CYBER COOPERATION IN THE FRAMEWORK OF THE ASEAN REGIME - Obet, Dedy; Suharto, Suharto; Mujoko, Henri (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The COVID-19 pandemic has a given significant impact on both economics and internet-based digital services in Southeast Asia. It also applied to cross-border nontraditional security issues such as cyber-attacks that evolve continuously. The complexity of prevention acts towards cyber threats in Southeast Asia is quite complicated. Therefore, the ASEAN countries should form strong cooperation due to many anonymous and impromptu attacks. This research aims to analyze cyber cooperation within the ASEAN framework. The method applied in this article is the qualitative method, by accumulating data through earlier literature and studies. The outcome of this analysis shows the mechanism to perform cyber cooperation is through the ASEAN regional forum known as ARF (ASEAN Regional Forum) as the organizer of ASEAN countries' interactions in eliminating cyber-attacks. This research gives conclusions that the proposed mechanism should be flexible, multi-dimensional, and taking accounts from the economics point of view.Â